Composer’s Work with Verbal Component in Vocal Opus in Aspect of the Language Levels Theory - Ivanova, Inna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research. The composer’s work with a verbal source in vocal composition can be viewed from two positions. The first of them concerns the structure of the text, its components and their characteristics, punctuation, the specifics of visual graphics etc. The other position connects with meaning and interpretation. When semantic component is considered, the traditional methods, which were formed mainly on the material of the classical and romantic period, remain basic. For vocal compositions of the 20th –21st centuries composers’ work with the structure of the verbal source becomes indicative. But it is impossible to explain these changes with traditional analytical tools. Therefore, it is necessarily to form original method of vocal compositions analysis, which directs for fixing and explaining such structural changes. The purpose of the study. The purpose of the article is presentation of analyzing method of composers’ work with a verbal component in a vocal opus based on the linguistic concept of language levels. Methods. The article uses general scientific and special scientific research methods. Among the general scientific methods descriptive, comparative, systemic are used. Among the special ones structural and functional are used. The structural method gives possible to consider verbal language as a four-level structure that exists due to a combination of located at different levels elements. The functional method is involved to identify the primary function of each of the elements and made by composer changes. The results and conclusions. A composer has possibility to work with verbal text on four language levels: phonological, morphological, lexical-semantic and syntactic. Each level requires attention to its basic elements: phonemes, morphemes, words and sentences. Accordingly, analyzing the element with which a composer works, we reach a certain language level. It gives for us possibility to understand what is important for the composer: to convey the meaning of the verbal series; to present one word from which all morphemes and phonemes will emerge; to demonstrate extraction of one phoneme, etc. Often composers are not limited to changes at one language level, but move from one to another one. The proposing method of analysis is demonstrated on the examples from vocal works by Ivan Karabits, Ludmila Yurina, Leonid Grabovskyi, Carola Bauckhold.